Determinação de resíduos de agrotóxicos em mel de abelhas (Apis sp.) por cromatografia gasosa acoplada à espectrometria de massas - Carla Martins Pittella (2009)
Among the problems concerning the quality of honey, are the physical and chemicalcharacteristics, the identification of the floral and geographical origin, the occurrence ofadulteration and contamination, especially with antibiotics and pesticides. The adequacy ofthese features to existing laws in the country makes the product more competitive for the exportmarket. This work aims the development of a multi residue methodology for the determinationof pesticides in honey, as a contribution to the improvement of methodologies for the analysis ofcontaminants described in Normative Instruction No 9, March 30, 2007 to MAPA and itsapplication in samples of honey from different regions of Brazil. The technique used was gaschromatography coupled to mass spectrometry, using SIM acquisition mode, electron ionization(EI) at 70 eV. Three techniques of extraction - liquid-liquid extraction, solid phase extraction(C18) and dispersive solid phase extraction modified "QuEChERS" was evaluated. The resultsof the extraction procedures indicated the interference of the matrix in the chromatographicresponses when compared with the analytical curve obtained only in ethyl acetate. Best analyteresponses were obtained for the liquid-liquid extraction with ethyl acetate. A method usingliquid-liquid extraction and analytical curves obtained in the matrix extract resuspended in ethylacetate was developed and validated for the 20 pesticides from the classes of organochlorinepesticides, organophosphates, carbamates and pyrethroids. In this work the followingparameters were assessed for validation of the method. Linearity of analytical curves (7concentration levels and six injections each). Analytical curves were obtained to adjustment forquadratic regression and determination coefficients higher than 0.989. Limit of detection (LOD)calculated ranged from 0,4 to 13,4 ng mL-1 and limit of quantification (LOQ) performedbetween 1,4 and 60,8 ng mL-1. The precision for the study of repetibilibidade (% RSD between3,4 and 32,9%) and accuracy (recovery rate - 92% a 115%). The fortifications of the sampleswere taken at three concentration levels (1,0 ìg kg-1, 5,0 ìg kg-1, 10,0 ìg kg-1). Themethodology was applied to the analysis of 46 honey samples from different regions of Brazil.It was detected the presence of pesticides in 8 samples. In three of them, the compounds foundmay be related to the use of pesticides on crops in the neighborhood of apiaries